Case report: A case of oviductal and uterine leiomyosarcoma in an 11-year-old dog - Kazmierczak, Jillian; Sugai, Nicole J.; Withowski, Katie E.; Jonatan, Abe; LeRoith, Tanya; Cecere, Julie T. (Frontiers in Veterinary Science, 2023)
An 11-year-old, intact female Pomeranian dog was presented for evaluation due to an 18-h history of anorexia and lethargy. Abdominal ultrasound revealed a 3×3 cm mass of mixed echogenicity at the level of the left ovary. At laparotomy, a 5 mm mass was identified at the cranial region of the right uterine horn and a 3 cm round mass was visualized near the cranial aspect of the left uterine horn. Ovariohysterectomy was performed. A diagnosis of grade 1 oviductal and uterine leiomyosarcoma was made via histopathology for both masses. Oviductal leiomyosarcomas are rare and generally locally invasive similar to other soft tissue sarcomas but do not often metastasize. Uterine leiomyosarcomas are also uncommon but are one of the more common tumors affecting the female reproductive tract. This is the only known case report of oviductal leiomyosarcoma in the dog and the only report of uterine leiomyosarcoma in addition to oviductal leiomyosarcoma as well. This case illustrates the oviduct as an additional site that can be affected by leiomyosarcoma and demonstrates surgery as a treatment option for patients diagnosed with this condition.